Human disturbance and shifts in vertebrate community composition in a biodiversity hotspot. Issue 2 (8th October 2021) - Vargas Soto, Juan S.; Beirne, Christopher; Whitworth, Andrew; Cruz Diaz, Juan Carlos; Flatt, Eleanor; Pillco‐Huarcaya, Ruthmery; Olson, Erik R.; Azofeifa, Alejandro; Saborío‐R, Guido; Salom‐Pérez, Roberto; Espinoza‐Muñoz, Deiver; Hay, Leslie; et al.
Abstract: Understanding how human modification of the landscape shapes vertebrate community composition is vital to understanding the current status and future trajectory of wildlife. Using a participatory approach, we deployed the largest camera‐trap network in Mesoamerica to date to investigate how anthropogenic disturbance shapes the occupancy and co‐occurrence of terrestrial vertebrate species in a tropical biodiversity hotspot: the Osa Peninsula, Costa Rica. We estimated species richness in different categories of land protection with rarefaction analysis and estimated the expected occupancy with a joint species distribution model that included covariates for anthropogenic disturbance, land protection, habitat quality, and habitat availability. Areas with the most stringent land‐use protections (e.g., Corcovado National Park, 24 species [95% CI 23–25]) harbored significantly more species than unprotected areas (20 species [19.7–20.3]), mainly due to a reduced presence of large‐bodied species of conservation concern in unprotected areas (e.g., jaguar Panthera onca and white‐lipped peccary Tayassu pecari ). Small‐bodied generalist species, such as opossums (Didelphidae) and armadillos ( Dasypus novemcinctus ), in contrast, were more common at disturbed sites, resulting in a significant difference in vertebrate community composition between sites with low and high disturbance. Co‐occurrence of species was also mainly associated with response to disturbance. Similar responses to disturbance create two groups of species, those whose site‐level occupancy usually increased as anthropogenic disturbance increased and those whose estimated occupancy decreased. The absence of large‐bodied species entails an important loss of ecological function in disturbed areas and can hinder forest development and maintenance. Efforts to protect and restore forested landscapes are likely having a positive effect on the abundance of some threatened species. These efforts, however, must be sustained and expanded to increase connectivity and ensure the long‐term viability of the wildlife community. Abstract : Perturbaciones Humanas y Cambios en la Composición de la Comunidad de Vertebrados en un Punto Caliente de Biodiversidad Resumen: El entendimiento de cómo las modificaciones humanas del paisaje conforman la composición de las comunidades de vertebrados es vital para entender el estado actual y la trayectoria futura de la fauna. Mediante una estrategia participativa, desplegamos la mayor red de cámaras trampa en Mesoamérica hasta la fecha para investigar cómo la perturbación antropogénica determina la ocupación y coocurrencia de las especies terrestres de vertebrados en un punto caliente de biodiversidad tropical: la Península de Osa, Costa Rica. Estimamos la riqueza de especies en diferentes categorías de protección de suelo con un análisis de rarefacción y estimamos la ocupación esperada con un modelo de distribución conjunta de especies que incluyó covariables para la perturbación antropogénica, la protección del suelo, la calidad del hábitat y la disponibilidad del hábitat. Las áreas con la protección más estricta de uso de suelo (p. ej.: Parque Nacional Corcovado, 24 especies [95% CI 23‐25]) albergaron significativamente a más especies que las áreas desprotegidas (20 especies [19.7‐20.3]), principalmente debido a la presencia reducida de especies de talla grande de interés para la conservación en las áreas desprotegidas (p. ej.: el jaguar Panthera onca, el pecarí de labios blancos, Tayassu pecari ). Al contrario, las especies generalistas de talla pequeña, como las zarigüeyas (Didelphidae) y el armadillo ( Dasypus novemcinctus ) fueron más comunes en los sitios perturbados, lo que resulta en una diferencia significativa en la composición de las comunidades de vertebrados entre los sitios con una perturbación baja y alta. La coocurrencia de especies también estuvo asociada principalmente con la respuesta a la perturbación. Las respuestas similares a la perturbación crean dos grupos de especies: aquellas cuya ocupación a nivel de sitio generalmente incrementó conforme incrementó la perturbación antropogénica y aquellas cuya ocupación estimada disminuyó. La ausencia de especies de talla grande conlleva una pérdida importante de la función ecológica en las áreas perturbadas y puede dificultar el desarrollo y mantenimiento del bosque. Los esfuerzos para proteger y restaurar los paisajes forestales probablemente estén teniendo un efecto positivo sobre la abundancia de algunas especies amenazadas. Estos esfuerzos, sin embargo, deben ser sostenidos y expandidos para incrementar la conectividad y asegurar la viabilidad a largo plazo de la comunidad faunística. 摘要: 理解人类对景观的改变如何塑造脊椎动物群落组成对于了解野生动物的现状和未来轨迹至关重要。本研究使用参与式方法, 在中美洲部署了迄今为止最大的红外相机监测网络, 以调查人为干扰如何影响热带生物多样性热点地区——哥斯达黎加奥萨半岛的陆生脊椎动物分布和共存情况。我们通过稀疏性分析估算了不同保护类型的土地的物种丰富度, 并利用联合物种分布模型对物种分布区占有率进行了估计, 该模型的协变量包括人为干扰、土地保护、栖息地质量和栖息地可用性。土地利用保护最严格的区域(如科尔科瓦多国家公园, 有 24 个物种 [95%置信区间为23‐25])的物种数量明显多于未保护区域 (20个物种 [19.7‐20.3]), 这主要是由于未保护区域内大型保护动物数量减少(如美洲豹 Panthera onca 、白唇西猯 Tayassu pecari )。相反, 体型较小的广生性物种, 如负鼠 (Didelphidae) 和犰狳( Dasypus novemcinctus ), 则在受干扰地区更为常见, 这导致低干扰和高干扰位点之间脊椎动物群落组成产生显著差异。物种的共存也与其对干扰的响应有重要关系。根据对干扰的相似响应可以将物种分为两类, 一类物种的分布区占有率随人为干扰增加而增加, 另一类物种的占有率则下降。大型动物的缺失会导致受干扰地区生态功能严重丧失, 并可能阻碍森林的发展与维持。森林景观的保护和恢复可能会促进受威胁物种的丰度增加。然而, 我们还需要持续且更大范围的努力来增加连通性, 以保障野生动物群落的长期生存力。【翻译: 胡怡思;审校: 聂永刚】